Occupational risk factors for skin cancer and the availability of sun protection measures at German outdoor workplaces - Ruppert, LInda; Ruppert, Linda M.; Ofenloch, Robert; Surber, Christian; Diepgen, Thomas L. (International archives of occupational and environmental health, 2016)
Germany implemented a new occupational disease “squamous cell carcinoma or multiple actinic keratosis due to natural UV radiation (UVR)” into the German ordinance on occupational diseases. Since primary prevention is very important, the aim of this study was to assess the provision of sun protection measures by the employers in vocational school students for outdoor professions.
Gesehen am 06.05.2020